THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY AND INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE - Seowidasari, Jesslyn; Ekadjaja, Agustin (International Journal of Application on Economics and Business, 2025)
The objective of this study is to gather empirical data about how corporate social responsibility with intellectual capital affect economic performance of banking institutions that are listed on Indonesia Stock Exchange (IDX) between 2018 and 2022. In this study, 10 samples and 50 data points from banking businesses were chosen using the purposive sampling method. Microsoft Excel 2016 and the SPSS Version 25 software were used for data collection and analysis. The study's conclusions show that corporate social responsibility along with intellectual capital have a favourable yet substantial impact on financial success.